HUBUNGAN TERPAAN IKLAN ROKOK DI TELEVISI DENGAN SIKAP REMAJA KOTA DENPASAR TERHADAP ROKOK - Candra, Shelviani; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT According to the WHO data in 2018, the number of smokers in Indonesia is the third highest in the world (WHO, 2008). The hypothesis says the influence of advertising is one of the factors that cause teens to smoke. These studies use quantitative methods of positivist paradigm is associative. The sampling technique is a non-probability sampling and the method used is the purposive sampling. The data obtained by disseminating a questionnaire. From the results of data analysis through the SPSS program, there are three interpretations, firstly the relationship between Ho an H1 is stated to be very weak. Second, the relationship between the two variables was declared insignificant. Third, the direction of the relationship is unknown because there is no significant relationship between variables X and Y in this study. So, in this study Ho is accepted and H1 is rejected. Key Words: Denpasar, Smoking, Television Commercials, Attitudes, Exposures